5.20.9 Problems 801 to 900

Table 5.923: Second or higher order ODE with constant coefficients

#

ODE

Mathematica

Maple

3148

\[ {}y^{\prime \prime }-2 y^{\prime }+y = {\mathrm e}^{2 x} \]

3149

\[ {}y^{\prime \prime }+y = 4 \sin \left (2 x \right ) \]

3150

\[ {}y^{\prime \prime }+4 y = 2 x -2 \sin \left (2 x \right ) \]

3151

\[ {}y^{\prime \prime }-y = 3 x +5 \,{\mathrm e}^{x} \]

3152

\[ {}y^{\prime \prime }+9 y = {\mathrm e}^{x}+\sin \left (4 x \right ) \]

3153

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }-4 y^{\prime } = \cos \left (2 x \right ) \]

3154

\[ {}y^{\prime \prime \prime }+4 y^{\prime \prime }-5 y^{\prime } = {\mathrm e}^{3 x} \]

3155

\[ {}y^{\prime \prime }+y = \tan \left (x \right ) \]

3156

\[ {}y^{\prime \prime }+a^{2} y = \sec \left (a x \right ) \]

3157

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }+y^{\prime } = {\mathrm e}^{2 x} \]

3158

\[ {}y^{\prime \prime \prime \prime }-2 y^{\prime \prime \prime }+y^{\prime \prime } = x^{2} \]

3159

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }-4 y^{\prime } = {\mathrm e}^{2 x}+\sin \left (x \right ) \]

3160

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{x}}{\left (1-x \right )^{2}} \]

3161

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = \sin \left ({\mathrm e}^{-x}\right ) \]

3162

\[ {}y^{\prime \prime }+4 y = \sec \left (x \right ) \tan \left (x \right ) \]

3163

\[ {}y^{\prime \prime }-2 y = {\mathrm e}^{-x} \sin \left (2 x \right ) \]

3164

\[ {}y^{\prime \prime }+9 y = \sec \left (x \right ) \csc \left (x \right ) \]

3165

\[ {}y^{\prime \prime }+9 y = \csc \left (2 x \right ) \]

3166

\[ {}y^{\prime \prime }+y = \tan \left (\frac {x}{3}\right )^{2} \]

3167

\[ {}y^{\prime \prime \prime }+y^{\prime } = \tan \left (x \right ) \]

3168

\[ {}4 y^{\prime \prime }-4 y^{\prime }+y = {\mathrm e}^{\frac {x}{2}} \ln \left (x \right ) \]

3170

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = {\mathrm e}^{3 x} \]

3171

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = {\mathrm e}^{x} \]

3172

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = x^{2} \]

3173

\[ {}y^{\prime \prime }+4 y = 2 \,{\mathrm e}^{x} \]

3174

\[ {}y^{\prime \prime }+3 y = 3 \,{\mathrm e}^{-4 x} \]

3175

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = \frac {{\mathrm e}^{x}}{2}+\frac {{\mathrm e}^{-x}}{2} \]

3176

\[ {}y^{\prime \prime }+y^{\prime }-2 y = {\mathrm e}^{-2 x} \]

3177

\[ {}y^{\prime \prime }+2 y = \sin \left (x \right ) \]

3178

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = \frac {{\mathrm e}^{3 x}}{2}-\frac {{\mathrm e}^{-3 x}}{2} \]

3179

\[ {}y^{\prime \prime }+3 y^{\prime }-2 y = \sin \left (2 x \right ) \]

3180

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = {\mathrm e}^{x} \sin \left (x \right ) \]

3181

\[ {}y^{\prime \prime \prime }-y = {\mathrm e}^{x} \]

3182

\[ {}y^{\prime \prime \prime }-4 y^{\prime \prime }+y^{\prime }-4 y = \sin \left (x \right )-{\mathrm e}^{4 x} \]

3183

\[ {}y^{\prime \prime \prime \prime }+3 y^{\prime \prime }-4 y = 4 \,{\mathrm e}^{x}+3 \cos \left (2 x \right ) \]

3184

\[ {}y^{\prime \prime }+y = {\mathrm e}^{3 x} \left (1+\sin \left (2 x \right )\right ) \]

3185

\[ {}y^{\prime \prime }+2 n^{2} y^{\prime }+n^{4} y = \sin \left (k x \right ) \]

3186

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = \frac {{\mathrm e}^{x}}{2}+\frac {{\mathrm e}^{-x}}{2} \]

3187

\[ {}y^{\prime \prime }+y^{\prime }-2 y = x \,{\mathrm e}^{-x} \]

3188

\[ {}y^{\prime \prime }+4 y = x \,{\mathrm e}^{x} \]

3189

\[ {}y^{\prime \prime }+2 y = x^{2} {\mathrm e}^{-x} \]

3190

\[ {}y^{\prime \prime }-y^{\prime }-2 y = x^{2}-8 \]

3191

\[ {}y^{\prime \prime \prime }-y = x^{2} \]

3192

\[ {}y^{\prime \prime \prime }+4 y^{\prime \prime }-5 y^{\prime } = x^{2} {\mathrm e}^{-x} \]

3193

\[ {}y^{\prime \prime \prime \prime }-2 y^{\prime \prime \prime }+y^{\prime \prime } = x^{2} \]

3194

\[ {}y^{\prime \prime \prime }-y^{\prime } = {\mathrm e}^{x} \left (\sin \left (x \right )-x^{2}\right ) \]

3195

\[ {}y^{\prime \prime \prime }-4 y^{\prime \prime } = {\mathrm e}^{2 x} \left (x -3\right ) \]

3196

\[ {}y^{\prime \prime \prime \prime }-6 y^{\prime \prime \prime }+9 y^{\prime \prime } = \sin \left (3 x \right )+x \,{\mathrm e}^{x} \]

3197

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y = x^{2} {\mathrm e}^{2 x} \]

3198

\[ {}y^{\prime \prime \prime }+2 y^{\prime } = x^{2}+\cos \left (x \right ) \]

3199

\[ {}y^{\prime \prime \prime \prime }+3 y^{\prime \prime }-y^{\prime }+2 y = \sin \left (2 x \right ) \]

3200

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y^{\prime } = x^{3}-\frac {\cos \left (2 x \right )}{2} \]

3201

\[ {}y^{\prime \prime \prime }+4 y^{\prime \prime }+5 y^{\prime } = {\mathrm e}^{-2 x} \cos \left (x \right ) \]

3202

\[ {}y^{\prime \prime \prime }+y^{\prime \prime }-2 y^{\prime } = {\mathrm e}^{-2 x} \cos \left (2 x \right ) \]

3203

\[ {}y^{\prime \prime \prime }+2 y^{\prime } = x^{2} \sin \left (x \right ) \]

3204

\[ {}y^{\prime \prime \prime \prime }-y = x^{2} \cos \left (x \right ) \]

3205

\[ {}y^{\prime \prime }+4 y = x \sin \left (x \right ) \]

3206

\[ {}y^{\prime \prime }+y = x^{2} \cos \left (x \right ) \]

3207

\[ {}y^{\prime \prime }-y = x^{2} \cos \left (x \right ) \]

3208

\[ {}y^{\prime \prime \prime }+4 y^{\prime } = {\mathrm e}^{x}+\sin \left (x \right ) \]

3209

\[ {}y^{\left (5\right )}+y^{\prime \prime \prime \prime } = x^{2} \]

3210

\[ {}2 y^{\prime \prime }+3 y^{\prime }-2 y = {\mathrm e}^{x} x^{2} \]

3211

\[ {}y^{\prime \prime \prime }+y^{\prime } = \sin \left (x \right ) \]

3212

\[ {}y^{\prime \prime \prime }-y^{\prime } = x \sin \left (x \right ) \]

3213

\[ {}y^{\prime \prime \prime }+2 y^{\prime \prime } = x \cos \left (2 x \right ) \]

3214

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = x^{2} \cos \left (x \right ) \]

3215

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = x^{2} \sin \left (x \right ) \]

3216

\[ {}y^{\prime \prime }-y = \sin \left (2 x \right ) x \]

3217

\[ {}y^{\prime \prime }+2 y^{\prime } = x^{3} \sin \left (2 x \right ) \]

3218

\[ {}y^{\prime \prime }-y^{\prime } = x \,{\mathrm e}^{2 x} \sin \left (x \right ) \]

3219

\[ {}y^{\prime \prime }-4 y = x \,{\mathrm e}^{2 x} \cos \left (x \right ) \]

3220

\[ {}y^{\prime \prime }+2 y^{\prime } = x^{2} {\mathrm e}^{-x} \sin \left (x \right ) \]

3244

\[ {}y^{\prime \prime } = \cos \left (t \right ) \]

3245

\[ {}y^{\prime \prime } = k^{2} y \]

3246

\[ {}x^{\prime \prime }+k^{2} x = 0 \]

3266

\[ {}y^{\prime \prime } = y \]

3272

\[ {}y^{\prime \prime } = \sec \left (x \right ) \tan \left (x \right ) \]

3282

\[ {}x^{\prime \prime }-k^{2} x = 0 \]

3484

\[ {}x^{\prime \prime }+\omega _{0}^{2} x = a \cos \left (\omega t \right ) \]

3485

\[ {}f^{\prime \prime }+2 f^{\prime }+5 f = 0 \]

3486

\[ {}f^{\prime \prime }+2 f^{\prime }+5 f = {\mathrm e}^{-t} \cos \left (3 t \right ) \]

3487

\[ {}f^{\prime \prime }+6 f^{\prime }+9 f = {\mathrm e}^{-t} \]

3488

\[ {}f^{\prime \prime }+8 f^{\prime }+12 f = 12 \,{\mathrm e}^{-4 t} \]

3489

\[ {}f^{\prime \prime }+8 f^{\prime }+12 f = 12 \,{\mathrm e}^{-4 t} \]

3490

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 4 \,{\mathrm e}^{-x} \]

3491

\[ {}y^{\prime \prime \prime }-12 y^{\prime }+16 y = 32 x -8 \]

3496

\[ {}y^{\prime \prime }-y = x^{n} \]

3497

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 2 x \,{\mathrm e}^{x} \]

3558

\[ {}y^{\prime \prime }-25 y = 0 \]

3559

\[ {}y^{\prime \prime }+4 y = 0 \]

3560

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 0 \]

3563

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 0 \]

3564

\[ {}y^{\prime \prime }-9 y = 0 \]

3570

\[ {}y^{\prime \prime }-\left (a +b \right ) y^{\prime }+y a b = 0 \]

3571

\[ {}y^{\prime \prime }-2 a y^{\prime }+a^{2} y = 0 \]

3572

\[ {}y^{\prime \prime }-2 a y^{\prime }+\left (a^{2}+b^{2}\right ) y = 0 \]

3573

\[ {}y^{\prime \prime }-y^{\prime }-6 y = 0 \]

3574

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

3584

\[ {}y^{\prime \prime } = x \,{\mathrm e}^{x} \]

3585

\[ {}y^{\prime \prime } = x^{n} \]